2018
DOI: 10.1186/s13031-018-0166-9
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based financing in three humanitarian settings: principles and pragmatism

Abstract: BackgroundPerformance based financing (PBF) has been increasingly implemented across low and middle-income countries, including in fragile and humanitarian settings, which present specific features likely to require adaptation and to influence implementation of any health financing programme. However, the literature has been surprisingly thin in the discussion of how PBF has been adapted to different contexts, and in turn how different contexts may influence PBF. With case studies from three humanitarian setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 25 publications
0
52
0
Order By: Relevance
“…Context has played an important role in the story of PBF-N. This observation is not atypical for an intervention in a FCAS and has been documented in other studies on PBF in such settings [16,[63][64][65].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Context has played an important role in the story of PBF-N. This observation is not atypical for an intervention in a FCAS and has been documented in other studies on PBF in such settings [16,[63][64][65].…”
Section: Discussionmentioning
confidence: 59%
“…Alongside evaluations focused on the impact of PBF [11][12][13], we have now studies investigating the actual theories of change, with a plurality of situations and practices which prevail. One can highlight, for instance, the recent work by the ReBUILD team on how PBF works in Fragile and post-Conflict Affected Settings (FCAS) [14][15][16], the comprehensive analysis of the RBF scheme in Malawi by De Allegri and colleagues [17] or the research program carried out by Borghi and colleagues, mainly in Tanzania [18].…”
Section: Introductionmentioning
confidence: 99%
“…Such a transition has led to a reduction in verification costs in Zimbabwe by 47%. 15 PBF programmes are not static but continue through action research 30 to seek the best possible strategy towards improving the health system.…”
Section: Implementation Challengesmentioning
confidence: 99%
“…Some research has shown that analysing the PBF implementation process provides a better understanding of the outcomes achieved [21]. Recent studies have paid more attention to the impacts of PBF on the relationships among actors in the health system and to the contexts and processes that explain whether or not these outcomes are achieved [18,[22][23][24][25][26]. To understand the processes, the contextual characteristics of implementation are essential elements and warrant in-depth analysis [27].…”
Section: Introductionmentioning
confidence: 99%